To solve for x, we need to isolate the variable x.
First, let's distribute the -5/3 to both terms inside the parentheses:
3 - (5/3)x = 18
Next, we can move the constant term (3) to the other side of the equation by subtracting 3 from both sides:
- (5/3)x = 18 - 3
Simplifying the right side of the equation gives:
- (5/3)x = 15
Now, let's multiply both sides of the equation by -3/5 to solve for x:
(-3/5)(- 5/3)x = (-3/5)(15)
The -5/3 and 3 in the numerator and denominator of the left side cancel out, leaving only x:
x = (-3/5)(15)
Multiplying the values on the right side:
x = -45/5
Simplifying the fraction by dividing the numerator and denominator by their greatest common divisor of 5:
x = -9
Therefore, x = -9 is the solution to the equation.
Solve for x .
3−5/3x=18
1 answer